A Note on the Heterogeneous Choice Model. (February 2015) - Rohwer, Goetz
The heterogeneous choice model (HCM) has been proposed as an extension of the standard logit and probit models, which allows taking into account different error variances of explanatory variables. In this note, I show that in an important special case, this model is just another way to specify an interaction effect.